A method for preparing a high-strength and high-conductivity copper-based composite material for a lead frame

By using atomization condensation, mechanical alloying and solid-liquid stirring in copper-chromium zirconium alloys, a variety of oxide-strengthening phases are added to solve the problem of degradation in the conductivity of existing copper-chromium zirconium alloys, and a high-strength and high-conductivity copper-based composite materials are realized, meeting the high-performance needs of the lead frame.

CN115846672BActive Publication Date: 2025-04-22HEFEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211499400.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2025-04-22
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

While the existing copper-chromium-zirconium alloys increase hardness and strength, their conductivity decreases and cannot meet the needs of high-performance lead frames.

Method used

By combining atomization condensation and mechanical alloying, by adding a variety of oxide-strengthening phases, using solid-liquid stirring and high-temperature calcining processes, the oxide-enhanced phases are uniformly dispersed, the mechanical properties of the material are improved and the high conductivity is maintained.

Benefits of technology

The high-strength and high-conductance comprehensive performance of copper-based composite materials is achieved, which meets the application needs of lead frames, improves the mechanical properties of the materials and maintains high conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115846672B_ABST
    Figure CN115846672B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-strength and high-conductivity copper-based composite material for a lead frame, which uses a combination of atomization condensation and mechanical alloying to obtain a large amount of precursor materials with trace elements uniformly distributed on a copper matrix; further, a process of solid-liquid stirring and high-temperature calcination is used to obtain a copper-based composite powder with a plurality of reinforcing phases dispersedly distributed through oxidation and precipitation decomposition, which is conducive to subsequent sintering and grain refinement, and obtains a copper-based composite material with better interface bonding, greatly improves the mechanical properties of the material and maintains the electrical conductivity at a high level, further improving the performance of the copper-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of copper-based alloy preparation, and specifically relates to a method for preparing a high-strength and high-conductivity copper-based composite material for a lead frame. The copper-based composite material of the present invention is mainly used as a material for commutators, magnetic field conductive devices, integrated circuit lead frames, etc., especially for integrated circuit lead frames. Background Art

[0002] As the chip carrier of integrated circuits, the lead frame can connect the lead end and the lead end of the internal circuit of the chip through bonding materials, and plays a vital role in the entire electronic product manufacturing process. Due to its excellent mechanical and electrical properties, copper-chromium-zirconium alloy can be used as the lead of electronic discrete components, maintaining excellent strength and conductivity when hermetically sealed. The current mainstream method is to prepare oxide dispersion-strengthened copper alloys, and further improve the hardness and strength of copper-chromium-zirconium alloys by adding oxide second phases, but traditional additions are prone to cause a significant decrease in the conductivity of the material, and cannot guarantee its excellent mechanical and electrical comprehensive properties. With the continuous development of semiconductor technology, the performance requirements of materials are getting higher and higher. A new method is needed to prepare copper-based composite materials, improve their comprehensive performance, and enable them to be further applied in the lead frame industry. In the study, it was found that compared with adding a single oxide strengthening phase to the copper matrix, adding multiple oxide strengthening phases to achieve the effect of composite strengthening further improved the performance of copper-based composite materials. Different from the traditional method of directly adding multiple reinforcing phases, the combination of atomization condensation and mechanical alloying can obtain large quantities of precursor materials with trace elements evenly distributed on the copper matrix; further, the process of solid-liquid mixing and high-temperature calcination can obtain copper-based composite powders with dispersed distribution of multiple reinforcing phases through oxidation and precipitation decomposition, which is beneficial to the subsequent sintering and grain refinement, and finally obtain copper-based composite materials with better interface bonding. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a high-strength and high-conductivity copper-based composite material for a lead frame. The method for preparing the CuCrZr-Y2O3-La2O3 copper-based composite material can not only improve the mechanical properties of the material, but also ensure that the electrical conductivity of the material does not decrease significantly and is within the range that meets the use requirements.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] The method for preparing the high-strength and high-conductivity copper-based composite material for a lead frame of the present invention comprises the following steps:

[0006] Step 1: Ingot Melting and Mixing

[0007] The copper-yttrium alloy ingot is placed in the vacuum melting furnace of the gas atomization furnace. In order to transmit high-power electricity, the charge is first added to one-third of the furnace. When the temperature rises above 800°C, the charge is continued. Then, the molten metal liquid is poured from the melting furnace into the tundish crucible under vacuum conditions and kept warm for a period of time.

[0008] Step 2: Atomization and condensation

[0009] The mixed molten metal is introduced into a high-pressure gas atomizer through a conduit, and the liquid metal flow is broken into small droplets by a high-speed airflow, and then quickly condensed to obtain spherical powder, which is finally collected by a cyclone separator to obtain a Cu-based alloy spherical powder supersaturated with dispersed phase element Y, namely, Cu-Y alloy powder;

[0010] Step 3: Mechanical alloying

[0011] A certain amount of Cu-Y alloy powder, chromium powder and zirconium powder are placed in a ball mill according to a certain ratio. The ball mill is first placed in a transition chamber of a glove box. After three vacuuming and argon filling operations, the air in the ball mill is successfully replaced with argon to prevent oxidation of the powder during the ball milling process. Carbide grinding balls are placed in the ball mill according to a ball-to-powder mass ratio of 5:1 to 10:1. After the ball mill is packaged in the glove box, it is placed in a high-energy ball mill for mechanical alloying to finally obtain a CuCrZr-Y composite powder. The Cu-Y alloy powder, chromium powder and zirconium powder are proportioned according to a ratio of Cu-0.9wt%Cr-0.4wt%Zr-(0.4-2.0)wt%Y;

[0012] Step 4: Solid-liquid mixing

[0013] Dissolve an appropriate amount of CuCrZr-Y alloy powder and lanthanum nitrate hexahydrate powder in deionized water, add a polytetrafluoroethylene rotor after sufficient stirring, then place the beaker in an oil bath in a magnetic stirrer and heat to 160-200°C, after all the deionized water in the beaker is evaporated, place the beaker in an oven at 110-130°C and dry for 8-16 hours to remove the remaining water, and obtain a pure precursor powder;

[0014] Step 5: High temperature calcination

[0015] The precursor powder obtained in step 4 is placed in a high-temperature tube furnace, calcined and reduced in a hydrogen atmosphere, and taken out after cooling in the furnace to finally obtain a CuCrZr-Y2O3-La2O3 composite powder;

[0016] Step 6: Field Assisted Plasma Sintering

[0017] Weigh 10g-14g of the CuCrZr-Y2O3-La2O3 composite powder obtained in step 5 and put it into a graphite mold. Wrap the powder and the mold with a layer of carbon paper and place two round pieces of carbon paper between the powder and the upper and lower pressure heads to prevent adhesion. After pre-pressing, put it into a spark plasma sintering equipment and evacuate it to a vacuum. Then heat it to 600°C and keep it warm for 5 minutes for exhaust treatment; then heat it to 900°C and keep it warm for 5 minutes to finally obtain a uniform phase. After the insulation is completed, cool it to room temperature to obtain a CuCrZr-Y2O3-La2O3 copper-based composite material.

[0018] In step 1, the purity of the copper ingot used to prepare the copper-yttrium alloy ingot is 99.9%, and the purity of the yttrium ingot is 99.9%.

[0019] In step 1, to ensure that the copper-yttrium alloy is completely melted, the melting temperature is set to 1500-1600°C, the tundish temperature is set to 1200-1300°C, the holding time is set to 8-10 minutes, and the atomization pressure is set to 5 MPa.

[0020] In step 2, in order to control the uniformity of the powder particle size, the diameter of the flow guide tube is controlled to be 3 mm.

[0021] In step 2, the liquid alloy is broken into small droplets by a high-speed airflow, and then quickly condensed to obtain a spherical powder, which is sieved by a cyclone separator to obtain a dispersed phase element Y supersaturated Cu-based alloy powder (Cu-Y) between 325 mesh (45 μm) and 500 mesh (25 μm).

[0022] In step 3, the vacuum glove box model is ZKX, and the planetary ball mill is QM-QX4 omnidirectional planetary ball mill produced by Nanjing University of Science and Technology.

[0023] In step 3, the ball milling speed (rotation speed) is 250-350 rpm / min, the ball milling time is 15-25 hours, and the ball milling jar and the ball milling medium are both made of high wear-resistant hard alloy YG6.

[0024] In step 4, the mass ratio of the two oxide reinforcement phases, Y2O3 and La2O3, is controlled to be 1:1.

[0025] In step 4, the contents of CuCrZr-Y alloy powder and lanthanum nitrate hexahydrate powder are formulated according to CuCrZr-1-5wt% (Y2O3-La2O3), such as CuCrZr-1wt% (Y2O3-La2O3), CuCrZr-3wt% (Y2O3-La2O3) or CuCrZr-5wt% (Y2O3-La2O3).

[0026] In step 5, the tube furnace model is GSL-1200X, and the hydrogen flow rate is 350-450 ml / min.

[0027] In step 5, the calcination reduction process is that the temperature is raised from room temperature to 580°C to 620°C at a rate of 10°C per minute and kept at this temperature for 1 to 3 hours before cooling with the furnace.

[0028] In step 6, the radius of the mold is 10 mm, and the thickness of the final circular block material is 5 mm.

[0029] In step 6, the sintering furnace model of field-assisted plasma sintering is LaboxTM-300, the pre-pressure during sintering is 10 MPa, and the maximum pressure is 50 MPa.

[0030] In step 6, the heating rate of field-assisted plasma sintering is 100°C / min. The temperature is raised to 600°C and then kept at this temperature for 5 minutes. After the temperature is kept at this temperature, the temperature is raised to 900°C and then kept at this temperature for 5 minutes. During the heating process, the pressure is manually and evenly applied to complete the process from pre-pressing to final pressing, and then the furnace is cooled to room temperature.

[0031] The beneficial effects of the present invention are embodied in:

[0032] Traditionally, adding a single strengthening phase to the matrix is ​​prone to agglomeration, and stress concentration is generated near the agglomerated strengthening phase, which destroys the mechanical properties of the matrix. Compared with adding a single strengthening phase to the copper matrix, adding multiple oxide strengthening phases to achieve the effect of composite strengthening is more conducive to improving the mechanical properties of the material. And unlike the traditional direct addition of multiple strengthening phases, the combination of atomization condensation and mechanical alloying can obtain a large number of precursor materials with trace elements uniformly distributed on the copper matrix; further adopting the process of solid-liquid stirring and high-temperature calcination can obtain a copper-based composite powder with a dispersed distribution of multiple strengthening phases by oxidation and precipitation decomposition, which is conducive to subsequent sintering and grain refinement, and obtains a copper-based composite material with better interface bonding, which greatly improves the mechanical properties of the material and maintains the electrical conductivity at a high level, further improving the performance of the copper-based composite material. The composition design and preparation process of the present invention achieve the excellent comprehensive performance of high strength and high conductivity of copper-based materials, meeting the application requirements of lead frame copper alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the surface SEM image of CuCrZr-3wt% (Y2O3-La2O3) composite powder at 5000 times.

[0034] Figure 2 This is the metallographic structure diagram of the CuCrZr-3wt% (Y2O3-La2O3) alloy block at 500 times.

[0035] Figure 3 This is the fracture morphology of the CuCrZr-3wt% (Y2O3-La2O3) alloy block at 2000 times. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific embodiments.

[0037] Embodiment 1:

[0038] The CuCrZr-Y2O3-La2O3 composite material in this embodiment is made by ingot melting and mixing, atomization condensation, mechanical alloying, solid-liquid stirring, high-temperature calcination, and field-assisted plasma sintering, wherein the ratio of each material is CuCrZr-1wt% (Y2O3-La2O3).

[0039] The preparation method of the CuCrZr-Y2O3-La2O3 composite material in this embodiment is as follows:

[0040] 1. Ingot melting and mixing: Place the copper-yttrium alloy ingot in the vacuum melting furnace of the gas atomization furnace. In order to deliver high-power electricity, the charge is first added to one-third of the furnace. When the temperature rises above 800°C, continue to add charge. Then, under vacuum conditions, pour the molten metal from the melting furnace into the tundish crucible and keep it warm for a period of time. The melting temperature is 1500°C, the tundish temperature is 1200°C, the insulation time is 8 minutes, and the atomization pressure is set to 5MPa.

[0041] 2. Atomization condensation: The mixed molten metal is introduced into a high-pressure gas atomizer through a conduit, and the liquid metal flow is broken into small droplets by a high-speed airflow, and then quickly condensed to obtain a spherical powder, which is finally collected by a cyclone separator to obtain a dispersed phase element Y supersaturated Cu-based spherical powder with a particle size of 325 mesh (45μm), namely, a Cu-Y alloy powder;

[0042] 3. Mechanical alloying: Take a certain amount of Cu-Y alloy powder, chromium powder and zirconium powder in proportion and put them into a ball mill. The ball mill is first placed in a transition chamber of a glove box. After three vacuuming and argon filling operations, the air in the ball mill is successfully replaced with argon to prevent oxidation of the powder during the ball milling process. Carbide grinding balls are placed in the ball mill at a ball-to-powder mass ratio of 5:1. After the ball mill is packaged in the glove box, it is placed in a high-energy ball mill for mechanical alloying to finally obtain a CuCrZr-Y composite powder. The Cu-Y alloy powder, chromium powder and zirconium powder are proportioned according to the ratio of Cu-0.9wt%Cr-0.4wt%Zr-0.4wt%Y. The ball milling speed (rotation speed) is 250rpm / min, and the ball milling time is 15 hours.

[0043] 4. Solid-liquid stirring: dissolve an appropriate amount of CuCrZr-Y alloy powder and lanthanum nitrate hexahydrate powder with a final composition of CuCrZr-1wt% (Y2O3-La2O3) in deionized water, add a polytetrafluoroethylene rotor after sufficient stirring, then place the beaker in an oil bath in a magnetic stirrer and heat to 160°C. After all the deionized water in the beaker is evaporated, place the beaker in an oven at 110°C and dry for 8 hours to remove the remaining moisture to obtain a pure precursor powder.

[0044] 5. High-temperature calcination: The precursor powder obtained above was placed in a high-temperature tube furnace, calcined and reduced in a hydrogen atmosphere, and then taken out after cooling in the furnace to finally obtain a CuCrZr-1wt% (Y2O3-La2O3) composite powder. The hydrogen flow rate was 350ml / min, and the temperature was increased from room temperature to 580°C at a rate of 10°C per minute and kept at this temperature for 1 hour, and then cooled in the furnace.

[0045] 6. Field-assisted plasma sintering: Weigh 10 g of the CuCrZr-Y2O3-La2O3 copper-based composite powder obtained in the above steps and put it into a graphite mold. Wrap the powder and the mold with a layer of carbon paper and place two round pieces of carbon paper between the powder and the upper and lower pressure heads to prevent adhesion. After pre-pressing, put it into a discharge plasma sintering equipment and evacuate it to a vacuum. Then heat it to 600°C and keep it warm for 5 minutes for exhaust treatment; then heat it to 900°C and keep it warm for 5 minutes to finally obtain a uniform phase. After the insulation is completed, cool it to room temperature to obtain a CuCrZr-1wt% (Y2O3-La2O3) copper-based composite material.

[0046] Embodiment 2:

[0047] The CuCrZr-Y2O3-La2O3 composite material in this embodiment is made by ingot melting and mixing, atomization condensation, mechanical alloying, solid-liquid stirring, high-temperature calcination, and field-assisted plasma sintering, wherein the ratio of each material is CuCrZr-3wt% (Y2O3-La2O3).

[0048] The preparation method of the CuCrZr-Y2O3-La2O3 composite material in this embodiment is as follows:

[0049] 1. Ingot melting and mixing: Place the copper-yttrium alloy ingot in the vacuum melting furnace of the gas atomization furnace. In order to deliver high-power electricity, the charge is first added to one-third of the furnace. When the temperature rises above 800°C, continue to add charge. Then, under vacuum conditions, pour the molten metal from the melting furnace into the tundish crucible and keep it warm for a period of time. The melting temperature is 1550°C, the tundish temperature is 1250°C, the insulation time is 9 minutes, and the atomization pressure is set to 5MPa.

[0050] 2. Atomization condensation: The mixed molten metal is introduced into a high-pressure gas atomizer through a conduit, and the liquid metal flow is broken into small droplets by a high-speed airflow, and then quickly condensed to obtain a spherical powder, which is finally collected by a cyclone separator to obtain a dispersed phase element Y supersaturated Cu-based spherical powder with a particle size of 400 mesh (38μm), namely, a Cu-Y alloy powder;

[0051] 3. Mechanical alloying: Take a certain amount of Cu-Y alloy powder, chromium powder and zirconium powder in proportion and put them into a ball mill. The ball mill is first placed in a transition chamber of a glove box. After three vacuuming and argon filling operations, the air in the ball mill is successfully replaced with argon to prevent oxidation of the powder during the ball milling process. Carbide grinding balls are placed in the ball mill at a ball-to-powder mass ratio of 7:1. After the ball mill is packaged in the glove box, it is placed in a high-energy ball mill for mechanical alloying to finally obtain a CuCrZr-Y alloy composite powder. The Cu-Y alloy powder, chromium powder and zirconium powder are proportioned according to the ratio of Cu-0.9wt%Cr-0.4wt%Zr-1.2wt%Y. The ball milling speed (rotation speed) is 300rpm / min and the ball milling time is 20 hours.

[0052] 4. Solid-liquid stirring: dissolve an appropriate amount of CuCrZr-Y composite powder and lanthanum nitrate hexahydrate powder with a final composition of CuCrZr-3wt% (Y2O3-La2O3) in deionized water, add a polytetrafluoroethylene rotor after sufficient stirring, then place the beaker in an oil bath in a magnetic stirrer and heat to 180°C. After all the deionized water in the beaker is evaporated, place the beaker in an oven at 120°C for 12 hours to remove the remaining moisture to obtain a pure precursor powder.

[0053] 5. High-temperature calcination: The precursor powder obtained above is placed in a high-temperature tube furnace, calcined and reduced in a hydrogen atmosphere, and taken out after cooling in the furnace to finally obtain a CuCrZr-3wt% (Y2O3-La2O3) composite powder. The hydrogen flow rate is 400ml / min, and the temperature is increased from room temperature to 600°C at a rate of 10°C per minute and kept for 2 hours, and then cooled in the furnace.

[0054] 6. Field-assisted plasma sintering: Weigh 12 g of the CuCrZr-Y2O3-La2O3 copper-based composite powder obtained in the above steps and put it into a graphite mold. Wrap the powder and the mold with a layer of carbon paper and place two round pieces of carbon paper between the powder and the upper and lower pressure heads to prevent adhesion. After pre-pressing, put it into a discharge plasma sintering equipment and evacuate it to a vacuum. Then heat it to 600°C and keep it warm for 5 minutes for exhaust treatment; then heat it to 900°C and keep it warm for 5 minutes to finally obtain a uniform phase. After the insulation is completed, cool it to room temperature to obtain a CuCrZr-3wt% (Y2O3-La2O3) copper-based composite material.

[0055] Embodiment 3:

[0056] The CuCrZr-Y2O3-La2O3 composite material in this embodiment is made by ingot melting and mixing, atomization condensation, mechanical alloying, solid-liquid stirring, high-temperature calcination, and field-assisted plasma sintering, wherein the ratio of each material is CuCrZr-5wt% (Y2O3-La2O3).

[0057] The preparation method of the CuCrZr-Y2O3-La2O3 composite material in this embodiment is as follows:

[0058] 1. Ingot melting and mixing: Place the copper-yttrium alloy ingot in the vacuum melting furnace of the gas atomization furnace. In order to deliver high-power electricity, the charge is first added to one-third of the furnace. When the temperature rises above 800°C, continue to add charge. Then, under vacuum conditions, pour the molten metal from the melting furnace into the tundish crucible and keep it warm for a period of time. The melting temperature is 1600°C, the tundish temperature is 1300°C, the insulation time is 10 minutes, and the atomization pressure is set to 5MPa.

[0059] 2. Atomization condensation: The mixed molten metal is introduced into a high-pressure gas atomizer through a conduit, and the liquid metal flow is broken into small droplets by a high-speed airflow, and then quickly condensed to obtain a spherical powder, which is finally collected by a cyclone separator to obtain a dispersed phase element Y supersaturated Cu-based spherical powder with a particle size of 500 mesh (25μm), namely, a Cu-Y alloy powder;

[0060] 3. Mechanical alloying: Take a certain amount of Cu-Y alloy powder, chromium powder and zirconium powder in proportion and put them into a ball mill. The ball mill is first placed in a transition chamber of a glove box. After three vacuuming and argon filling operations, the air in the ball mill is successfully replaced with argon to prevent oxidation of the powder during the ball milling process. Carbide grinding balls are placed in the ball mill at a ball-to-powder mass ratio of 10:1. After the ball mill is packaged in the glove box, it is placed in a high-energy ball mill for mechanical alloying to finally obtain a CuCrZr-Y composite powder. The Cu-Y alloy powder, chromium powder and zirconium powder are proportioned according to the ratio of Cu-0.9wt%Cr-0.4wt%Zr-2.0wt%Y. The ball milling speed (rotation speed) is 350rpm / min and the ball milling time is 25 hours.

[0061] 4. Solid-liquid stirring: Dissolve an appropriate amount of CuCrZr-Y alloy powder and lanthanum nitrate hexahydrate powder with a final composition of CuCrZr-5wt% (Y2O3-La2O3) in deionized water, add a polytetrafluoroethylene rotor after sufficient stirring, and then place the beaker in an oil bath in a magnetic stirrer and heat it to 200°C. After all the deionized water in the beaker is evaporated, place the beaker in an oven at 130°C for 16 hours to remove the remaining moisture to obtain a pure precursor powder.

[0062] 5. High-temperature calcination: The precursor powder obtained above was placed in a high-temperature tube furnace, calcined and reduced in a hydrogen atmosphere, and then taken out after cooling in the furnace to finally obtain a CuCrZr-5wt% (Y2O3-La2O3) composite powder. The hydrogen flow rate was 450ml / min, and the temperature was increased from room temperature to 620°C at a rate of 10°C per minute and kept for 3 hours, and then cooled in the furnace.

[0063] 6. Field-assisted plasma sintering: Weigh 14 g of the CuCrZr-Y2O3-La2O3 copper-based composite powder obtained in the above steps and put it into a graphite mold. Wrap the powder and the mold with a layer of carbon paper and place two round pieces of carbon paper between the powder and the upper and lower pressure heads to prevent adhesion. After pre-pressing, put it into a discharge plasma sintering equipment and evacuate it to a vacuum. Then heat it to 600°C and keep it warm for 5 minutes for exhaust treatment; then heat it to 900°C and keep it warm for 5 minutes to finally obtain a uniform phase. After the insulation is completed, cool it to room temperature to obtain a CuCrZr-5wt% (Y2O3-La2O3) copper-based composite material.

[0064] Table 1 Electrical conductivity, Vickers hardness and tensile strength of CuCrZr-Y2O3-La2O3 composite materials in Examples 1 to 3

[0065]

[0066] Depend on Figure 1 It can be seen that many fine protruding particles appear on the surface of the copper-chromium-zirconium powder. The components are yttrium oxide and lanthanum oxide after analysis, indicating that the CuCrZr-Y2O3-La2O3 composite powder with dispersed distribution of Y2O3 and La2O3 is successfully obtained using this method.

[0067] Depend on Figure 2 It can be seen that the yttrium oxide and lanthanum oxide particles are pinned on the copper grain boundaries, which inhibits the growth of copper grains during sintering and improves the comprehensive properties of the composite material.

[0068] Depend on Figure 3 It can be seen that the fracture surface of CuCrZr-3wt% (Y2O3-La2O3) mainly presents dimple morphology, with a large number of small dimples, which is an obvious ductile fracture, indicating that the two reinforcement phases are well combined with the copper matrix, improving the mechanical properties of the material.

[0069] It can be seen from Table 1 that the mechanical properties of various oxide dispersion-strengthened copper-based composite materials prepared by ingot melting and mixing, atomization condensation, mechanical alloying, solid-liquid stirring, and high-temperature calcination are significantly improved with less loss of electrical conductivity.

Claims

1. A method for preparing a high-strength and high-conductivity copper-based composite material for a lead frame, characterized in that The steps include: Step 1: Ingot Melting and Mixing The copper-yttrium alloy ingot is placed in a vacuum melting furnace of a gas atomization furnace. The charge is first added to one third of the furnace. When the temperature rises to above 800°C, the charge is continued. Then, the molten metal is poured from the melting furnace into the tundish crucible under vacuum conditions and kept warm for a period of time. Step 2: Atomization and condensation The mixed molten metal is introduced into a high-pressure gas atomizer through a conduit, and the liquid metal flow is broken into small droplets by a high-speed airflow, and then quickly condensed to obtain spherical powder, which is finally collected by a cyclone separator to obtain a Cu-based spherical powder supersaturated with dispersed phase element Y, i.e., Cu-Y alloy powder; Step 3: Mechanical alloying Take a certain amount of Cu-Y alloy powder, chromium powder and zirconium powder according to a proportion, put them into a ball mill, put in a hard alloy grinding ball, and perform mechanical alloying in an argon atmosphere to finally obtain a CuCrZr-Y composite powder. The Cu-Y alloy powder, chromium powder and zirconium powder are mixed in a ratio of Cu-0.9wt%Cr-0.4wt%Zr-(0.4-2.0)wt%Y; Step 4: Solid-liquid mixing Dissolve an appropriate amount of CuCrZr-Y alloy powder and lanthanum nitrate hexahydrate powder in deionized water, stir thoroughly and add a polytetrafluoroethylene rotor, then place the beaker in an oil bath in a magnetic stirrer and heat to 160-200°C, after all the deionized water in the beaker evaporates, place the beaker in an oven at 110-130°C and dry for 8-16 h to remove the remaining water, and obtain a pure precursor powder; Step 5: High temperature calcination The precursor powder obtained in step 4 is placed in a high-temperature tube furnace, calcined and reduced in a hydrogen atmosphere, and taken out after cooling in the furnace to finally obtain a CuCrZr-Y2O3-La2O3 composite powder; Step 6: Field Assisted Plasma Sintering Weigh 10g-14g of the CuCrZr-Y2O3-La2O3 composite powder obtained in step 5 and put it into a graphite mold, wrap the powder and the mold with a layer of carbon paper, and place two round pieces of carbon paper between the powder and the upper and lower pressure heads to prevent adhesion. After pre-pressing, put it into a spark plasma sintering equipment and evacuate it to a vacuum, then heat it to 600°C and keep it warm for 5 minutes for exhaust treatment; then heat it to 900°C and keep it warm for 5 minutes, and finally obtain a uniform phase. After the insulation is completed, cool it to room temperature to obtain a CuCrZr-Y2O3-La2O3 copper-based composite material; In step 1, to ensure that the copper-yttrium alloy is completely melted, the melting temperature is set to 1500-1600°C, the tundish temperature is set to 1200-1300°C, the holding time is set to 8-10 minutes, and the atomization pressure is set to 5 MPa; In step 2, the liquid metal is crushed by a high-speed airflow to form small droplets, which are then rapidly condensed to obtain spherical powders, which are then sieved by a cyclone separator to obtain a dispersed phase element Y supersaturated Cu-based alloy powder between 325 meshes and 500 meshes; In step 4, the content of CuCrZr-Y alloy powder and lanthanum nitrate hexahydrate powder is proportioned according to CuCrZr-1-5wt% (Y2O3-La2O3), and the mass ratio of the two oxide reinforcement phases Y2O3 and La2O3 is controlled to be 1:

1.

2. The preparation method according to claim 1, characterized in that: In step 2, in order to control the uniformity of the powder particle size, the diameter of the flow guide tube is controlled to be 3 mm.

3. The preparation method according to claim 1, characterized in that: In step 3, the ball milling speed is 250-350 rpm / min, the ball powder mass ratio is 5:1-10:1, and the ball milling time is 15-25 hours.

4. The preparation method according to claim 1, characterized in that: In step 5, the calcination reduction process is that the temperature is raised from room temperature to 580°C-620°C at a rate of 10°C per minute and kept at this temperature for 1-3 hours and then cooled with the furnace.

5. The preparation method according to claim 1, characterized in that: In step 6, the pre-pressure during field-assisted plasma sintering is 10 MPa and the maximum pressure is 50 MPa.

6. The preparation method according to claim 1, characterized in that: In step 6, the heating rate of field-assisted plasma sintering is 100°C / min. The temperature is raised to 600°C and then kept at this temperature for 5 minutes. After the temperature is kept at this temperature, the temperature is raised to 900°C and then kept at this temperature for 5 minutes. During the heating process, the pressure is manually and evenly applied to complete the process from pre-pressing to final pressing, and then the furnace is cooled to room temperature.

Citation Information

Patent Citations

  • Liquid-liquid doped rare earth oxide copper-based composite material and preparation method thereof

    CN107217171A

  • Preparation method for Y2O3-doped reinforced CuCrZr alloy

    CN113355550A

  • Cu-(Y2O3-HfO2) alloy with excellent performance and preparation method thereof

    CN115044794A